Influence of various material parameters on the abrasion re- sistance of concrete by sand blasting - Kumar, G B Ramesh; Sharma, Umesh Kumar; Bhardwaj, Arjit (Journal of Asian Concrete Federation, 2017)
In the present study, the abrasion resistance of concrete containing low quality aggregates was investigated and various ways and means were recommended to enhance the abrasion resistance of concrete on the basis of experimental results. Strength grade of concrete, type and quantity of pozzolana, type of ag- gregates and cement type were taken as different variables and their effects on the performance of concrete against abrasion were investigated. Three types of aggregates with different Los Angeles (L.A.) abrasion values (less than 30%, between 30% and 50% and more than 50%) were employed in this study. A total of 60 cubes were tested to evaluate the abrasion resistance of concrete and corresponding 60 cubes were tested for the evaluation of cube compressive strength. Results show that the abrasion resistance of concrete is af- fected adversely as L.A. abrasion value of aggregates increases but no direct correlation exists between abra- sion resistance of concrete and L.A. abrasion value of aggregates. As the L.A. abrasion value of aggregates exceeds a value of 30%, there was a considerable decrement in abrasion resistance of resulting concrete. Im- portant observations have been made about the role of pozzolanic additions on abrasion resistance of con- crete made with weak aggregates.